2020
DOI: 10.1016/j.atherosclerosis.2020.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Electronic cigarettes containing nicotine increase endothelial and platelet derived extracellular vesicles in healthy volunteers

Abstract: The vascular effects of e-cigarettes with and without nicotine were investigated in healthy volunteers. • Circulating extracellular vesicles (EVs) of endothelial and platelet origin were assessed. • Thirty puffs of nicotine-containing e-cigarette vapor caused an increase in EVs of endothelial and platelet origin. • Following exposure to e-cigarettes without nicotine only platelet derived EVs expressing CD40 ligand were increased. • E-cigarettes cause stress to endothelial and platelet cells similar to what has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 54 publications
3
27
0
1
Order By: Relevance
“…Corsello et al also showed airway epithelial cells exposed to environmental tobacco smoke displayed an increase in EV size that further lead to enhanced EV cargo content [49]. Furthermore, a recent study examining the effects of e-cigarettes containing nicotine revealed an increase in endothelial and platelet-derived EVs in healthy volunteers [50]. Our current observation that chronic nicotine treatment caused an increase in both BDEV concentration and size in males and females further bolsters these above-mentioned studies.…”
Section: Discussionsupporting
confidence: 80%
“…Corsello et al also showed airway epithelial cells exposed to environmental tobacco smoke displayed an increase in EV size that further lead to enhanced EV cargo content [49]. Furthermore, a recent study examining the effects of e-cigarettes containing nicotine revealed an increase in endothelial and platelet-derived EVs in healthy volunteers [50]. Our current observation that chronic nicotine treatment caused an increase in both BDEV concentration and size in males and females further bolsters these above-mentioned studies.…”
Section: Discussionsupporting
confidence: 80%
“…The one study that assessed HR variability found a sympathetic predominance in those individuals exposed to e-cigarettes containing nicotine, a pattern associated with increased cardiac risk in populations with and without known cardiovascular disease (Moheimani et al 2017). A similar cross-over study by Mobarrez et al (2020) observed increased platelet and endothelial derived extracellular vesicles 4 h following exposure to inhalation of e-cigarettes with nicotine, which is consistent with activation of platelets by acute e-cigarette exposure. In another crossover study (Chaumont et al 2018), occasional smokers were randomized to short-term (acute) exposure to high-wattage nicotine-free e-cigarette use, e-cigarette use with nicotine and sham use.…”
Section: Acute Exposures (Max 60 Min)mentioning
confidence: 76%
“…Interestingly, CD40 expression on plate-derived EVs was also increased by e-cigarette vapor that did not contain nicotine. The study concluded that as few as 30 puffs from a nicotine-containing e-cigarette caused an increase in circulating EVs that originated from endothelial or platelet cells, and nicotine, as a component of the vapor, affects EV formation and protein composition [130].…”
Section: Nicotinementioning
confidence: 99%
“…With the increasing use of electronic cigarettes (e-cigarettes), it is important to understand how this form of smoking may affect EVs and their cargoes. A recent study found that platelet- and endothelial-derived EVs were increased 4 h after active inhalation of e-cigarette vapor with nicotine [ 130 ]. Further, platelet-derived EVs expressing P-selectin, a platelet activation marker, and CD40, an inflammation marker, were significantly increased following inhalation of e-cigarette vapor with nicotine.…”
Section: Drugs Of Abusementioning
confidence: 99%